Study of Microstructure and Mechanical Properties of As-built and Heat-treated Additive Manufactured Inconel 718 Alloy - Ajay Kumar Maurya; Amit Kumar (Universitas Gadjah Mada, 2021)
Additive manufacturing technology is becoming popular in the industry because it allows the manufacturer to fabricate cost-effective, strong, lightweight, and complex-shaped parts directly from 3D design data as compared with the conventional manufacturing method. Inconel 718 alloy is the most demanding material in aviation as well as in the automobile industry, in terms of manufacturing high-performance parts. In this study, Inconel 718 samples were built using the direct metal laser sintering process, and standard heat treatment was performed on the samples to improve their microstructure and mechanical properties. The as-built samples exhibited good grain structure with fine laves phases, but the matrix was free from ?' and ?